Prognostic Value and Potential Role of Alternative mRNA Splicing Events in Cervical Cancer - Shao, Xiang-yang; Dong, Jin; Zhang, Han; Wu, Ying-song; Zheng, Lei (Frontiers in Genetics, 2020)
Background: Increasing evidence suggests that aberrant alternative splicing (AS) events are associated with progression of cancer. This study evaluated the prognostic value and clarify the role of AS events in cervical cancer (CC). Methods: Based on RNA-seq AS event data and clinical information of CC patients in The Cancer Genome Atlas (TCGA) database, we sought to identify prognosis-related AS events in this setting. We selected several survival-associated AS events to construct a prognostic predictor for CC through the least absolute shrinkage and selection operator (LASSO) and multivariate Cox regression. Moreover, Kyoto Encyclopedia of Genes and Genomes and Gene Ontology analyses were performed on genes with prognosis-related AS events and constructed an AS-splicing factors (SFs) regulatory network. Results: 2770 AS events were significantly correlated with overall survival (OS). The area under the curve (AUC) values of receiver-operator characteristic curve (ROC) for the final prognostic predictor were 0.926, 0.946 and 0.902 at 3, 5 and 10 years, respectively. These values indicated efficiency in prognostic risk stratification for patients with CC. The final prognostic predictor was an independent predictor of OS (HR: 1.24; 95% CI: 1.020–1.504; P<0.05). The AS-SFs correlation network may reveal an underlying regulatory mechanism of AS events. Conclusions: AS events are essential participants in the prognosis of CC and hold great potentials for the prognostic stratification and development of treatment strategy.